2022
DOI: 10.1097/nne.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metaverse in Nursing Education

Abstract: Background: Given the wide range of metaverse technologies, there is a need to synthesize evidence of metaverse pedagogy used effectively for nursing education. Purpose: This umbrella review synthesized systematic reviews on the use of metaverse in nursing education. Methods: A search was performed in MEDLINE, EMBASE, CINAHL, Web of Science, and Education Full Text. This umbrella review was conducted with reference to the Joanna Briggs Institute (JBI) Reviewer's Manual and reported using Preferred Reporting It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…An umbrella review evaluating the use of metaverse technology in nursing education identified the application of virtual reality (VR) technology (desktop and IVR) as the primary technology medium being used to enhance simulated nursing education [43]. A systematic review by Shorey and Ng [44] evaluated the use of VR simulation among nursing students and registered nurses.…”
Section: Discussionmentioning
confidence: 99%
“…An umbrella review evaluating the use of metaverse technology in nursing education identified the application of virtual reality (VR) technology (desktop and IVR) as the primary technology medium being used to enhance simulated nursing education [43]. A systematic review by Shorey and Ng [44] evaluated the use of VR simulation among nursing students and registered nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual Reality (VR) simulation strategies are rapidly emerging as a crucial component of students' educational trajectory [14]. These strategies provide students with an enriched hands-on experience that is pivotal in their comprehensive understanding of the practical applications and limitations of AI in real-world settings [15].…”
Section: Virtual Reality Simulation Exercisesmentioning
confidence: 99%
“…(20) Por otro lado, para enfermedades crónicas como hipertensión, diabetes, obesidad y algunas condiciones de salud mental, los modelos de atención virtual con programas de apoyo psicológico grupal podrían ser una intervención válida, mientras que la atención de enfermería virtual remota con unidades robóticas de entrega al usuario final también podría ser de ayuda. (21) Obviamente las personas necesitan de un entorno en que sean capaces de realizar las actividades, herramientas y medios para cumplir las tareas indicadas. Carraro et al (22) y Petrigna et al (23) hacen referencia al uso de bicicletas estáticas, cintas corredoras y otros equipos que permiten la realización de carreras con el simultaneo uso de "Pelotón" una aplicación de realidad virtual que simula carreras y permite al usuario intercambiar con otros cibernautas que realizan igual actividad en otro lugar del mundo.…”
Section: Aplicaciones En La Prevención Y Control De Enfermedadesunclassified